ENHANCING RICE PRODUCTION EFFICIENCY THROUGH OPTIMIZED MACHINERY ALLOCATION IN KUBU RAYA, INDONESIA - Ekawati; Rizieq, R.; Purwanto, A.; Purwanto, Asti (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Optimizing the allocation of agricultural machinery is crucial for enhancing rice production efficiency, particularly in regions with uneven resource distribution. This study addresses the lack of localized, data-driven mechanization strategies in Kubu Raya Regency, bridging an important research gap in sustainable resource allocation. It focuses on Sungai Kakap and Kubu subdistricts in Kubu Raya Regency, West Kalimantan, to develop and prioritize the distribution of hand tractors, cultivators, and power threshers based on land area, cropping index, and existing saturation levels. Primary data were collected through structured interviews with a representative sample of agricultural stakeholders, while secondary data included rice production levels, machinery availability, and land use statistics. The results identified Tanjung Saleh and Kampung Baru as high-priority villages due to extensive paddy field areas, high cropping intensities, and critically low machinery saturation levels. Addressing these shortages can significantly enhance land preparation, planting efficiency, and post-harvest processing, leading to increased productivity and reduced operational costs. A validated coefficient approach and stakeholder engagement were integrated into the prioritization framework to ensure robust decision-making and policy relevance. The proposed prioritization framework offers a data-driven approach for equitable machinery distribution, supporting sustainable agricultural development and regional food security. Beyond Kubu Raya, these findings provide actionable insights for policymakers and practitioners seeking to refine agricultural resource allocation strategies in similar contexts. This study thus proposes a foundation for future research on optimizing agricultural mechanization, highlighting potential benefits for policy and practice at both local and broader scales.